STAGES OF PLASTIC DEFORMATION OF NEUTRON IRRADIATED 12CR18-NI10-TI STEEL - Tsay, K.V. (Хабаршы. Физика сериясы, 2018)
The stages of plastic deformation for 12Cr18Ni10Ti austenitic steel non-irradiated and irradiated with neutrons up to fluences 1.4´1019, 1.3´1020n/cm2 were determined based on the analysis of “true” deformation curves of the hardening coefficients and microstructural evolution. The character of development for both dislocation substructures and mechanical twins in irradiated steel was revealed at various local deformations.